Relationship between adequacy of prenatal care utilization - Zahra Bostani Khalesi; Fateme Rafat; sedigheh Pakseresht (Journal of Holistic Nursing and Midwifery)
Introduction: Inadequate and improper prenatal care may result in adverse neonatal outcomes. Various are implemented to evaluate the adequacy of prenatal care one of the new indices for accurate and comprehensive measurement is adequacy of prenatal care utilization index. Objective: The aim of this study is to determine the adequacy of prenatal care and its relationship with neonatal outcomes. Methods: This analytic historical cohort study was performed on 205 pregnant women referring to health centers in Rasht city. Data gathering instrument consisted of a four part questionnaire covering demographic data, data related to current pregnancy, data related to neonate and adequacy of prenatal care utilization index. Care was classified in four groups: intensive, adequate, moderate and inadequate. Data were analyzed using by descriptive statistics and, Chi-square and Spearman's correlation coefficients. Results: Most cases of preterm birth, fetal death, low birth weight, neonatal jaundice was in the group with inadequate prenatal care (p<0.05). There was no significant difference in four groups as regard to age, employment, education, body mass index and attendance of childbirth preparation classes. There was no significant difference found in four groups between height and head circumference at birth and adequacy of prenatal care. Conclusion: In attention to implementation of reducing number of referrals of pregnant mothers (based on Standardization Protocol for Mothers in Iran), this study, along with confirmation of effect of adequacy of prenatal care on reduction of neonatal outcomes, once again emphasizes on providing the minimum care (based on the National Protocol).